On the Effects of Private Information on Volatility - Anne Opschoor; Michel van der Wel; Dick van Dijk; Nick Taylor (Tinbergen Institute, 2011)
We study the impact of private information on volatility in financial markets. We develop a comprehensive framework to investigate this link while controlling for the effects of both public information (such as macroeconomic news releases) and private information on prices and the effects of public information on volatility. Using a high-frequency 30-year U.S. Treasury bond futures data set, we find that private information variables, such as order flow and bid-ask spread, are statistically and economically significant explanatory variables for volatility. Private information is more important than public information, with the effect of a shock to order flow on volatility being four times larger than the effect of a surprise in the most influential macroeconomic news announcement. Moreover, we document an interaction between public and private information effects on volatility, with the impact of order flow on volatility depending positively on the dispersion of analysts' expectations about macroeconomic announcements. Finally, we find that the effect of private information on volatility is larger during contractions than during expansions.
Keywords: G14; E1; 330; Information; macroeconomic announcements; order flow; Treasury futures; heterogeneity; Staatspapier; Volatilität; Asymmetrische Information; Wirtschaftsindikator; USA